The Prediction of Need for Achievement to Generate Entrepreneurial Intention: A Locus of Control Mediation - Kusumawijaya, Ida Ketut (International Review of Management and Marketing, 2019)
This study aims to predict the need for achievement to increase entrepreneurial intention by mediating locus of control of SME employees in Bali. This research was conducted on SME employees in Bali were selected by purposive sampling method with 190 respondents with a response rate of 100%. Research instruments based on the need for achievement, locus of control, entrepreneurial intention (Dinis et al., 2013). Each research instrument uses a 5 Likert scale measurement. The initial evaluation is carried out by estimating the evaluation of the measurement model, namely the validity and reliability of each reflective construct. The next evaluation was structural models for testing research models using the WarpPLS 4.0 program. The significance of the parameters is determined by resampling bootstrapping and using 500 sub-samples of equal size to that of the original sample. The results and discussion show that need for achievement is able to predict SME employee entrepreneurial intention in Bali, need for achievement can influence SME employee locus of control in Bali, locus of control has the ability to predict SME employee entrepreneurial intention in Bali, locus of control is able to mediate predictions need for achievement on SME employee entrepreneurial intention in Bali. Keywords: need for achievement, locus of control, entrepreneurial intention JEL Classifications: J52, L26 DOI: https://doi.org/10.32479/irmm.8330